Implementation of Design Thinking Method in Pediatric Specialist Clinic Service Innovation: Case Study of SPC Pediatric Clinic - Ahmad Ridwan; Mohammad Isa Irawan (Publikasi Indonesia, 2024)
This research aims to evaluate the implementation of the Design Thinking method in service innovation at SPC Pediatric Clinic. This method is applied to improve service quality and efficiency through five stages: Empathize, Define, Ideate, Prototype, and Test. Data were collected through interviews, observation, documentation, and questionnaires, then analysed using the Miles and Huberman model. The results showed that innovations such as online registration, home care services, health education, service specialisation, and partnerships with schools successfully improved patient satisfaction. Technical, coordination, and adaptation constraints were also identified but were overcome with gradual improvements. The overall implementation of these innovations had a positive impact on patient comfort and trust.